A comparative cost analysis of two screening strategies for colorectal cancer in Lynch Syndrome in a tertiary hospital, South Africa - Johnson, Yasmina (Health Economics Unit, 2017)
Individuals with Lynch Syndrome (LS) have a 25% to 75% lifetime risk of colorectal cancer and the cancer generally presents at an early age. Establishing the costs of strategies to prevent or delay the onset of cancer is, thus, desirable. This study compared the cost of two screening approaches - colonoscopy only (Strategy 1) versus genetic testing for LS followed by colonoscopy for the individuals that tested positive for LS (Strategy 2). A comparative cost analysis was conducted at a tertiary hospital, from the health provider perspective, using a micro-costing, ingredient approach. Probands that were selected, according to the Revised Bethesda Criteria, for genetic testing between 01 November 2014 and 30 October 2015, and their first degree relatives (high risk relatives) were evaluated according to Strategy 1 and Strategy 2. Total costs per strategy were estimated and compared. Sensitivity analyses were performed on adherence rates to colonoscopy, positivity rates of relatives and discount rates. A total of 40 families were studied. The total cost for Strategy 1 amounted to R4 932 718 ($332 617) compared to R390 308 ($26 319) for Strategy 2 (Discount rate 3%; Adherence 75% and Positivity rate of relatives 45%). Base case analysis indicated a difference of 92% less in the total cost for Strategy 2 compared to Strategy 1. Univariate sensitivity analyses showed that the difference in cost between the two strategies was not sensitive to changes in discount rates, adherence rates or positivity rates of relatives. Compared to colonoscopy screening only, colonoscopy combined with genetic testing presented a less costly option by identifying patients at high risk of colorectal cancer for screening. Testing of relatives should be facilitated since, compared to probands, genetic testing of relatives is less costly and is likely to have more benefit. Effectiveness of the screening programmes should be established through further research.